2012
DOI: 10.1371/journal.pone.0040921
|View full text |Cite
|
Sign up to set email alerts
|

Are There Neurophenotypes for Asthma? Functional Brain Imaging of the Interaction between Emotion and Inflammation in Asthma

Abstract: BackgroundAsthma is a chronic inflammatory disease noteworthy for its vulnerability to stress and emotion-induced symptom intensification. The fact that psychological stress and mood and anxiety disorders appear to increase expression of asthma symptoms suggests that neural signaling between the brain and lung at least partially modulates the inflammatory response and lung function. However, the precise nature of the neural pathways implicated in modulating asthma symptoms is unknown. Moreover, the extent to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 47 publications
(64 reference statements)
1
50
1
Order By: Relevance
“…In addition, the additive effect of atopic comorbidities in the inflammatory dysregulation may explain the dose-dependent relationship between a greater number of atopic comorbidities and a higher likelihood of subsequent depression and bipolar disorder. Finally, functional neuroimaging studies also supported the existence of this comorbidity between atopy and mood disorders (Rosenkranz et al, 2005;Ishiuji et al, 2009;Rosenkranz et al, 2012). Using functional magnetic resonance imaging, Ishiuji et al found that patients with atopic dermatitis exhibited bilateral activation of the anterior cingulate cortex (ACC), posterior cingulate cortex (PCC), and dorsolateral prefrontal cortex (DLPFC) (Ishiuji et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the additive effect of atopic comorbidities in the inflammatory dysregulation may explain the dose-dependent relationship between a greater number of atopic comorbidities and a higher likelihood of subsequent depression and bipolar disorder. Finally, functional neuroimaging studies also supported the existence of this comorbidity between atopy and mood disorders (Rosenkranz et al, 2005;Ishiuji et al, 2009;Rosenkranz et al, 2012). Using functional magnetic resonance imaging, Ishiuji et al found that patients with atopic dermatitis exhibited bilateral activation of the anterior cingulate cortex (ACC), posterior cingulate cortex (PCC), and dorsolateral prefrontal cortex (DLPFC) (Ishiuji et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Such connectivity may also be directly linked to airway inflammation in asthma. In a previous study, individuals with atopic asthma who were exposed to allergens had differential activation of the anterior insula by asthma-relevant emotional cues during the late phase of the dual response, and this differential activation was associated with airway inflammation (62).…”
Section: C/fpomentioning
confidence: 89%
“…It will be necessary to further explore the cellular and molecular events linking the corticosterone release to stress-induced immune regulation accelerating Th2-driven adaptive immunity. These investigations would further clarify the pathological role of the neuroendocrine-immune axis in psychological stress-related asthma exacerbation, leading to the development of new strategies for the treatment of specific asthma phenotypes such as psychiatry-related asthma [46,47]. …”
Section: Discussionmentioning
confidence: 99%